Robust detection of undifferentiated iPSC among differentiated cells - Keisuke Sekine (Nature Portfolio, 2020)
Abstract Recent progress in human induced pluripotent stem cells (iPSC) technologies suggest that iPSC application in regenerative medicine is a closer reality. Numerous challenges prevent iPSC application in the development of numerous tissues and for the treatment of various diseases. A key concern in therapeutic applications is the safety of the cell products to be transplanted into patients. Here, we present novel method for detecting residual undifferentiated iPSCs amongst directed differentiated cells of all three germ lineages. Marker genes, which are expressed specifically and highly in undifferentiated iPSC, were selected from single cell RNA sequence data to perform robust and sensitive detection of residual undifferentiated cells in differentiated cell products. ESRG (Embryonic Stem Cell Related), CNMD (Chondromodulin), and SFRP2 (Secreted Frizzled Related Protein 2) were well-correlated with the actual amounts of residual undifferentiated cells and could be used to detect residual cells in a highly sensitive manner using qPCR. In addition, such markers could be used to detect residual undifferentiated cells from various differentiated cells, including hepatic cells and pancreatic cells for the endodermal lineage, endothelial cells and mesenchymal cells for the mesodermal lineage, and neural cells for the ectodermal lineage. Our method facilitates robust validation and could enhance the safety of the cell products through the exclusion of undifferentiated iPSC.